Functional thinking shown by kindergarten students (Edma 0-6: Educación Matemática en la Infancia, 2017)
We present results from 12 kindergarten students (5-6 years old) of a private school in Granada. We work with them during three sessions using a design research methodology. In these sessions, we proposed the students three familiar situations, using different representations, and involving the functions y=x, y=2x, y=x+1. In the results, we show that these students evidenced functional thinking through correspondence and co-variation functional relationships. Some of the students perceived the patterns and achieved the generalization.
Keywords: Early Childhood Education; Pattern; Generalization; Functional thinking